How long is long-term priming? Classification and action priming in the scale of days. Issue 5 (May 2019) - Moutsopoulou, Karolina; Pfeuffer, Christina; Kiesel, Andrea; Yang, Qing; Waszak, Florian
Previous research has shown that stimulus–response associations comprise associations between the stimulus and the task (a classification task in particular) and the stimulus and the action performed as a response. These associations, contributing to the phenomenon of priming, affect behaviour after a delay of hundreds of trials and they are resistant against overwriting. Here, we investigate their longevity, testing their effects in short-term (seconds after priming) and long-term (24 hr and 1 week after priming) memory. Three experiments demonstrated that both stimulus–classification (S-C) and stimulus–action (S-A) associations show long-term memory effects. The results also show that retrieval of these associations can be modulated by the amount of engagement on the same task between encoding and retrieval, that is, how often participants performed this task between prime and probe sessions. Finally, results show that differences in processing time during encoding are linked to the amount of conflict caused during retrieval of S-C, but not S-A associations. These findings add new information to the existing model of priming as a memory system and pose questions about the interactions of priming and top-down control processes.